Does Susceptibility to the Numerosity Heuristic Impact Juror Assessments of Auditors' Liability?* - Joe, Jennifer R.; Luippold, Benjamin L.; Sanderson, Kerri‐Ann (Contemporary Accounting Research, 2022)
ABSTRACT We provide evidence that regulatory guidance aimed at improving audit efficiency and effectiveness—allowing auditor reliance on a multi‐location client's competent and objective internal audit function (IAF)—can unintentionally increase auditors' litigation risk. Our research is important in demonstrating how client characteristics and juror cognitive processing, such as the number of client locations and jurors' susceptibility to the numerosity heuristic, factors beyond auditors' control, can exacerbate their litigation exposure. Consistent with theoretical predictions, we find that susceptibility to the numerosity heuristic contributes to jurors assessing an increased likelihood of misstatement on multi‐location compared to single‐location audits. Furthermore, these assessments of higher misstatement risk on multi‐location audits lead jurors to perceive that auditor reliance on the client's IAF in multi‐location audits is less appropriate (i.e., not normal). Accordingly, jurors judge that auditors are more negligent when they rely on the IAF during multi‐location audits than when they do not, but IAF reliance does not impact auditor negligence on single‐location audits. Our results suggest auditor reluctance to use a qualified IAF, despite client pressure and regulatory allowance, can provide potential benefits to firms in terms of reduced litigation exposure. Thus, we demonstrate the legal regime can undermine the objectives of regulators' guidance to enhance audit efficiency and corporate governance.